2021
DOI: 10.1111/ijfs.15443
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of high‐intensity ultrasound and β‐cyclodextrin treatments on browning control in apple juice

Abstract: Summary This work evaluated the synergistic effects of combined high‐intensity ultrasound (HIU) with β‐cyclodextrin (β‐CD) treatments on inhibiting browning of apple juice and explored the mechanism through simulation system. The combined treatment of 300 W HIU with 0.006 g mL−1 β‐CD had a synergistic impact on maintaining juice colour, resulting in a 39.06% reduction in browning degree, only a 36.64% decrease in total phenolic content, and a 17.82% reduction in PPO activity. The inhibition of enzymatic browni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 350 MPa; 40 °C; length of exposure to pressure: 5–20 min PPO residual activities reduced to 10.91% for 5 min treatment, which further decreased to 0.12% after 10 min. [118] 3. Apple juice High pressure homogenisation PPO ProbeUS; 24 kHz; 100 µm amplitude; 7–45 min, Temperature – controlled (42 °C) and uncontrolled.…”
Section: Hurdle Approach- Us With Other Combined Technologiesmentioning
confidence: 99%
“… 350 MPa; 40 °C; length of exposure to pressure: 5–20 min PPO residual activities reduced to 10.91% for 5 min treatment, which further decreased to 0.12% after 10 min. [118] 3. Apple juice High pressure homogenisation PPO ProbeUS; 24 kHz; 100 µm amplitude; 7–45 min, Temperature – controlled (42 °C) and uncontrolled.…”
Section: Hurdle Approach- Us With Other Combined Technologiesmentioning
confidence: 99%
“…It provides vibrational energy which causes formation and collapse of bubbles and produces temporary spots during bubble implosion process, which then leads to cavitation. These conditions induce the enzymes’ structural change in the secondary and tertiary structures due to the interruption of hydrogen bond, van der Waals, hydrophobic interaction, electrostatic force in protein/enzyme, thus inhibiting the browning of fruits (Jiang et al., 2020; J. Zhang et al., 2022). Additionally, ultrasound can also inactivate the microbial activity in the fresh‐cut fruits and vegetables by two mechanisms: (a) the cavitation effect that breaks the cell walls, membrane structures, DNA of microbes, and (b) the free radical formation, such as hydroxyl radicals, from which hydrogen peroxide (antibacterial agent) can be formed through some reactions, and hydroxyl radicals can also react with the DNA of microbes (Nicolau‐Lapeña et al., 2019).…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%
“…Recently, a study investigated the effect of ultrasound treatment (100–400 W, 5–30 min) on enzymatic browning of apple juice (J. Zhang et al., 2022). It was found that ultrasound at 100 W was too weak to change or destroy the enzymes, and in contrast, it only promoted the interaction between enzymes and phenolics, resulting in higher BI.…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%
See 2 more Smart Citations